2020
DOI: 10.2147/ott.s252750
|View full text |Cite
|
Sign up to set email alerts
|

<p>Latest Advances of Long Non-Coding RNA SNHG5 in Human Cancers</p>

Abstract: Long non-coding RNAs (lncRNAs) have been potent regulators in the initiation and development of human cancers regarding their biological roles in the modulation of dosage compensation effect, epigenetics and cell differentiation. Recently, aberrant expression of lncRNA small nucleolar RNA host gene 5 (SNHG5) has been observed in various solid tumors, which was intently correlated with tumor range, metastasis, pathological stage and prognosis. Additional mechanical investigation disclosed that SNHG5 was involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
(148 reference statements)
1
9
0
Order By: Relevance
“…Further investigation was undertaken to determine the effects of SNHG5 on the release of inflammatory factors, such as IL-1β, IL-6, TNF-α and IL-10. The results of the present study were consistent with previously reported findings ( 9 ). The majority of the studies of SNHG5 are in the field of human cancer, including gastric, breast, liver and esophageal cancer ( 17 21 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Further investigation was undertaken to determine the effects of SNHG5 on the release of inflammatory factors, such as IL-1β, IL-6, TNF-α and IL-10. The results of the present study were consistent with previously reported findings ( 9 ). The majority of the studies of SNHG5 are in the field of human cancer, including gastric, breast, liver and esophageal cancer ( 17 21 ).…”
Section: Discussionsupporting
confidence: 94%
“…Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs that are >200 nucleotides in length and are involved in the regulation of several cellular processes ( 6 , 7 ), such as cell proliferation, apoptosis and differentiation, via regulating target gene expression ( 8 ). The lncRNA small nucleolar RNA host gene 5 (SNHG5) is a recently identified lncRNA that has yet to be extensively investigated, but has been found to be correlated with tumor range, metastasis, pathological stage and prognosis in various solid tumors ( 9 ). Moreover, SNHG5 has been indicated to play a key role in NP by sponging microRNA (miRNA/miR)-154-5p ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated whether RBM47 could function by binding lncRNA. LncRNA SNHG5 has been elucidated to exhibit oncogenic property in various cancers [ 38 41 ]. In this study, SNHG5 was downregulated in PTC, and overexpression of SNHG5 inhibited PTC cells proliferation, but activated autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG5 was reported as a pro-oncogenic factor stimulating proliferation of myeloid leukemia cells [ 62 ]. High expression of two snoRNAs, SNORA72 and SNORA26 , was correlated with pro-oncogenic properties of cells and poor prognosis in cancer [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%